2022
DOI: 10.2196/37790
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol Use in Patients With Osteoarthritis and Lower Back Pain: Infodemiology Study and Observational Analysis of Electronic Medical Record Data

Abstract: Background Lower back pain (LBP) and osteoarthritis (OA) are common musculoskeletal disorders and account for around 17.0% of years lived with disability worldwide; however, there is a lack of real-world data on these conditions. Paracetamol brands are frequently prescribed in France for musculoskeletal pain and include Doliprane, Dafalgan, and Ixprim (tramadol-paracetamol). Objective The objective of this retrospective study was to understand the journ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Prior studies showed no significant differences between acetaminophen and placebo in patients with low back pain or osteoarthritis in terms of pain, disability, or quality of life. The nonsteroidal anti-inflammatory drugs (NSAIDs) are not recommended in this age group because of the associated side effects on the cardiovascular system, renal impairment, and the increased risk of gastrointestinal bleeding [22].…”
Section: Challenges Of Pain Assessment and Management In Geriatric Pa...mentioning
confidence: 99%
“…Prior studies showed no significant differences between acetaminophen and placebo in patients with low back pain or osteoarthritis in terms of pain, disability, or quality of life. The nonsteroidal anti-inflammatory drugs (NSAIDs) are not recommended in this age group because of the associated side effects on the cardiovascular system, renal impairment, and the increased risk of gastrointestinal bleeding [22].…”
Section: Challenges Of Pain Assessment and Management In Geriatric Pa...mentioning
confidence: 99%
“…and palliative drug (NSAIDs, paracetamol, etc.) therapies to relieve pain symptoms. , However, an effective treatment for OA is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Management of pain due to CLBP or osteoarthritis is complex and generally includes a combination of pharmacological and nonpharmacological approaches, with varying results [13,14]. Pharmacological management includes paracetamol and nonsteroidal anti-infammatory drugs, and opioids have also been used, despite a lack of evidence of their efcacy [15,16]. Nonpharmacological approaches to pain management include exercise, yoga, acupuncture, and meditation [17].…”
Section: Introductionmentioning
confidence: 99%